Modality in Language Acquisition: Modalité et acquisition des langues - Dittmar, Norbert; Reich, Astrid; Reich, Astrid (Soziolinguistik und Sprachkontakt, 2011)
Modality in Language Acquisition / Modalité et acquisition des langues